Impact of Demographic factors: Strategies for Unorganized Players in the Steel Industry - Patel, Neerav; Chauhan, Rahul (Journal of Macroeconomics and Social Development, 2024)
The analysis investigates the impact of demographic factors—age, income, occupation, education, and gender—on variables within a sample population. While income, occupation, and gender show no significant differences among groups, education emerges as a significant determinant (F(3, 92) = 3.191, p = 0.027). Despite age not meeting conventional thresholds for significance, subtle trends suggest potential influence. These findings underscore the complex interplay of demographic factors in shaping outcomes, emphasizing the pivotal role of educational attainment. Nuanced approaches are necessary to unravel the multifaceted nature of demographic influences, informing targeted interventions and policies. Further research should delve deeper into the mechanisms underlying these relationships to promote equitable outcomes.